Fundamental Relation on Intuitionistic Fuzzy Γ-hypermodule - S. Abirami; S. Murugesan (International Journal of Mathematics And its Applications, 2015)
In this paper, we introduce and study the fundamental relation on intuitionistic fuzzy Γ-hypermodule as a generalization of the usual fuzzy Γ- hypermodule. Examples of fundamental relation on intuitionistic fuzzy Γ-hypermodule are constructed and some their proposition are proved.